2018
DOI: 10.1002/pssr.201800186
|View full text |Cite
|
Sign up to set email alerts
|

Light Tuning of the Resistance of NdNiO3 Films With CoFe2O4 Capping

Abstract: Metal–insulator transition (MIT) is generally thought to be difficult to alter once the material has been prepared. In this study, visible light is used to tune the resistance of NdNiO3 films, which are covered by granular CoFe2O4 capping, in an insulating state. With light illumination, the resistance of the NdNiO3 films is enhanced significantly at a low temperature of ≈9 K, which shows non‐volatile behavior. The magnitude of light‐induced resistance increase is dependent on the light wavelength and illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Most studies on RNO thus far have focused on the origin of the metal–insulator transition. , Ramanathan et al have explored the multifunctional applications of RNO, especially SmNiO 3 (SNO), in synaptic transistors, solid fuel cells, and electric-field sensors in salt water . However, up until now, little is known about potential applications of RNO in optoelectric devices, although the bandgap of RNO can be tuned by changing the A-site cation. We have previously reported that the bandgap of NdNiO 3 (NNO) can be continuously tuned by changing its oxygen content, leading to possible applications in photovoltaic devices. , It is thus of great scientific and technological interest to examine the effect of changing the A-site rare-earth element on photovoltaic response.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on RNO thus far have focused on the origin of the metal–insulator transition. , Ramanathan et al have explored the multifunctional applications of RNO, especially SmNiO 3 (SNO), in synaptic transistors, solid fuel cells, and electric-field sensors in salt water . However, up until now, little is known about potential applications of RNO in optoelectric devices, although the bandgap of RNO can be tuned by changing the A-site cation. We have previously reported that the bandgap of NdNiO 3 (NNO) can be continuously tuned by changing its oxygen content, leading to possible applications in photovoltaic devices. , It is thus of great scientific and technological interest to examine the effect of changing the A-site rare-earth element on photovoltaic response.…”
Section: Introductionmentioning
confidence: 99%